Hubungan antara Kecukupan Zat Gizi dengan Kemampuan Santri dalam Menghafal Al-Quran - Proverawati, Atikah; Munasib, Munasib; Awaludin, Adib Naufal (Matan : Journal of Islam and Muslim Society, 2025)
The ability to memorize each individual is different so that memorizing verses in the al-Quran takes different amounts of time. Memorization ability is one part of cognitive function that is influenced by individual factors. This study aimed to determine the relationship between nutritional adequacy on the ability to memorize al-Quran. This study was an observational study with a cross sectional. The number of samples in this study were 53 Islamic students who memorized al-Quran in Zam-zam Muhammadiyah Islamic Boarding School of Cilongok Banyumas. Sample selection was using purposive sampling technique based on inclusion and exclusion criteria. Nutritional adequacy variables were measured using Semi Quantitative Food Frequency Questionnaire (SQ-FFQ) and ability to memorize al-Quran using student memorization evaluation sheet. Data analyzed by Spearman Rank test. The results showed that there is no relationship between energy adequacy (p = 0,768), protein adequacy (p = 0,890), fat adequacy (p = 0,162), carbohydrate adequacy (p = 0,881), iron adequacy (p = 0,605), and zinc adequacy (p = 0,626) on the ability to memorize al-Quran.